Multifocal intelligence – the key to a flexible and creative school librarian (Confluenţe Bibliologice, 2026)
The article highlights the role of multifocal intelligence, a theory developed by Augusto Cury, in the work of the school librarian. In a world marked by rapid change and information overload, the librarian becomes an emotional mediator, a support for critical thinking, and a promoter of creativity. The text shows how integrating emotions, reason, and intuition helps prevent burnout and maintain inner balance. It also presents practical ways through which the librarian can develop a mental ﬁlter, manage diﬃcult situations, and transform the library into a safe, open, and student-centered space that fosters growth and development.
Keywords: school librarian; personal development; emotion management; critical thinking; interpersonal relations